A retrospective analysis of the effect of subcutaneous columellar strut graft on the nasal tip - Hussain Ibrahim Al-Obiedi, Salim; Salih khalaf, Amer (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the function of the columellar strut, and to evaluate its effect on the nasal tip. Method: The retrospective study was conducted from April to June 2022 at Al-Twifiq Private Hospital, Salaheddin Governorate, Iraq, and comprised data of patients who underwent closed septorhinoplasty between January 2021 and March 2022. Preoperative and 9-month postoperative imaging was used to follow up on those who required columella strut. Results: Of the 64 patients who underwent closed septorhinoplasty, 46(71.9%) received subcutaneous columellar strut; 32(69.6%) females and 14(30.4%) males with mean age 25±4.6 years (range: 19-41 years). The mean columella-labial angle preoperatively was 87.29±18.34 (range: 75-93o), and postoperatively it was 105.91±29.21 (range: (98-113o) (p<0.05.). Mean nasal tip projection before the operation was 0.59±0.19 (range: 0.48-0.62), and postoperatively it was 0.63±0.23 (range: (0.54-0.66) (p<0.05.). The appearance of the columellar show was corrected in 42(91.3%) patients. Conclusions: Subcutaneous columellar strut resulted in a distinct projection line of the nasal tip, increased rotation of the nasal tip, and correction of columella show. The graft placement via the subcutaneous route was found to be a simple and easy way with only a few disadvantages. Key Words: Columellar strut, Columella show, Closed septorhinoplasty, Nasal tip projection, Nasal tip rotation.